Development of In Situ Sensors for Chlorophyll Concentration Measurement. (30th April 2015) - Zeng, Lihua; Li, Daoliang
Abstract : Chlorophyll fluorescence measurement is a sensitive and effective method to quantify and analyze freshwater and sea water phytoplankton in situ . Major improvements in optical design, electronic technology, and calibration protocol have increased the accuracy and reliability of the fluorometer. This review briefly describes the improvement of probe design, excitation light sources, detectors, and calibrations of in situ fluorometers. Firstly, various optical designs for increasing the efficiency of fluorescence measurement are discussed. Next, the development of electronic technology to meet and improve in situ measurement, including various light sources, detectors, and corresponding measurement protocols, is described. In addition, various calibration materials, procedures, and methods are recommended for different kinds of water. The conclusion discusses key trends and future perspectives for in situ fluorescence sensors.